Faktor-Faktor yang mempengaruhi Stabilitas Harga Beras Soa di Kecamatan Soa Kabupaten Ngada - Dewi, Cintya Permata Mutiara; Nona, Reyna Virginia; Penu, Yustina Paulina (JURNAL EQUILIBRIUM, 2023)
This study aims to find out (1) Does the rice production process affect the price stability of Soa rice in Soa District (2) Does the demand for rice from outside the region affect the price stability of Soa rice (3) Does the availability of Bulog rice entering Soa District affect rice price stability Soa (4) Does riceproduction, demand for rice from outside the region and the availability of rice from the National Logistics Agency affect the price stability of Soa's rice. This research includes causality research using a quantitative approach. The sample in this study were 98 farmers. Data was collected by using a questionnaire that has been tested with classical assumptions. Multiple linear regression is used to test the research hypothesis. The results of this research show that, (1) There is a significant effect of rice production on the price stability of Soa rice with a value of 17.071 (2) There is a significant effect of demand for rice from outside the region on the price stability of Soa rice with a value of 3.493 (3) There is no significant effect on the price stability of Soa rice with a value of -11.323. Thevariables of rice production, demand for rice from outside the region and availability of rice from the National Logistics Agency significantly affect the pricestability variable of Soa rice with a significant value of 0.000<0.05.